SRR‐based polygon ring penta‐band fractal antenna for GSM/WLAN/WiMAX/ITU band applications. Issue 6 (June 2015) - Rajeshkumar, V.; Raghavan, Singaravelu
ABSTRACT: In this article, a compact split ring resonator‐based polygon ring fractal multiband antenna is presented. The operating frequencies of the proposed antenna are 1.8 GHz GSM, 2.4/5 GHz wireless local area network, 3.5 GHz worldwide interoperability for microwave access, and 7 GHz ITU bands. The self‐similarity fractal property and split rings are utilized in the regular 12‐sided polygon to get multiple frequency bands. Parametric studies are performed to study the effects of different parameters as well as to obtain the desired frequency bands with optimum performance. The proposed antenna with a compact size of 24 × 18 × 1.6 mm 3 is fabricated and tested to validate against simulation results. Measured antenna characteristic shows close agreement with the simulation. Also, uniform radiation characteristic is observed in the entire frequency bands of interest. © 2015 Wiley Periodicals, Inc. Microwave Opt Technol Lett 57:1301–1305, 2015